Indocyanine Green Lymphography, Lymphoscintigraphy, and Genetic Analysis in Nonsyndromic Primary Lymphedema: The Distal Dermal Backflow Grading System and the Print Sign - Mangialardi, Maria Lucia; Lorenzano, Valerio; Pagliara, Domenico; Visconti, Giuseppe; Gentileschi, Stefano; Salgarello, Marzia (Journal of Reconstructive Microsurgery, 2020)
Background Investigating correlations between clinical, instrumental, and genetic features of primary lymphedema (PL) with the aim to facilitate the diagnosis, the staging, and the management of this subgroup of patients.Methods A prospective observational study was conducted from September 2016 to May 2018, including patients with diagnosis of nonsyndromic PL. All patients underwent a lymphoscintigraphic rest-stress test, an indocyanine green (ICG) lymphographic test, and a genetic test from sputum sample.Results A total of 20 patients were enrolled in the study and 44 limbs were examined. The totality of clinically affected limbs (32/44) showed lymphographic and lymphoscintigraphic abnormalities. Concerning clinically healthy limbs (12/44), an abnormal pattern was demonstrated in 33.3% of ICG lymphographic test and 75% of lymphoscintigraphy. Regarding lymphography findings, the most frequent pattern was the distal dermal backflow (DDB). We distinguished four grades of DDB, which correlates with clinical and lymphoscintigraphic features. Furthermore, we found a new lymphographic alteration consisting of fluorescence appearing distally to the injection site of ICG, including fingers/toes and palmar/plantar surface of the hand and of the foot. This alteration, called “print sign,” seems to be typical of DDB pattern PL. Genetic test did not help us make any etiological diagnosis.Conclusion To our knowledge, this is the first study about PL comparing clinical, ICG lymphographic, lymphoscintigraphic, and genetic findings. As expected, all clinically affected limbs showed abnormalities in ICG lymphographic and lymphoscintigraphic tests. In opposition to what has previously been reported, also clinically healthy limbs showed lymphographic and lymphoscintigraphic alterations and this could suggest the existence of a subclinical form of PL. We proposed a grading of the DDB pattern, which correlates with clinical and lymphoscintigraphic features. Furthermore, we have described a new lymphographic alteration that seems to be typical of DDB pattern PL, the “print sign.”
Keywords: primary lymphedema; idiopathic lymphedema; lymphography